(untitled) (Journal of Parents and Teachers, 2014)
The author works conflicts and linguistics with different journalistic genres through various activities that can be carried out in the classroom. He gives very detailed examples showing that with journalistic texts it is possible to work on linguistic competences and skills. These activities show how to distinguish journalistic genres, how to elaborate linguistic comments on texts and how to elaborate opinion articles.